2012
DOI: 10.1051/0004-6361/201219365
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry induced by energetic ions in water ice mixed with molecular nitrogen and oxygen

Abstract: Context. Several molecular species have been observed as frozen gases in cold environments such as grains in the interstellar/circumstellar medium or icy objects in the outer solar system. Because N 2 and O 2 are homonuclear, symmetric molecules are not easily observed. It is therefore relevant to find indirect methods to prove their presence from astronomical observations. Aims. Here we investigate one of the possible indirect methods, namely the formation of specific molecules by cosmic ion bombardment of ic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 41 publications
0
27
0
Order By: Relevance
“…Specifically, the enhanced abundances of 10 Be, 7 Li and 21 Ne ( [292]; [102]) can only be explained by spallation reactions of solar energetic particles with O and C atoms of the Solar Nebula. Similarly, other short-lived nuclides, 36 Cl, 53 Mg and 41 Ca, are now explained in terms of irradiation from the early Sun (e.g. [283]; [185]).…”
Section: A Violent Start In a Crowded Violent Environmentmentioning
confidence: 99%
“…Specifically, the enhanced abundances of 10 Be, 7 Li and 21 Ne ( [292]; [102]) can only be explained by spallation reactions of solar energetic particles with O and C atoms of the Solar Nebula. Similarly, other short-lived nuclides, 36 Cl, 53 Mg and 41 Ca, are now explained in terms of irradiation from the early Sun (e.g. [283]; [185]).…”
Section: A Violent Start In a Crowded Violent Environmentmentioning
confidence: 99%
“…30 Nitric oxide has been identified in a number of different astrophysical regions, including star forming regions, 30 dark clouds, [31][32][33] hot cores, 34 PDRs, 35 and in the nucleus of the starburst galaxy NGC 253 -an extragalactic source. 36 [38][39][40] So far no evidence has been found that NO forms in non-energetic surface reactions like, for example, N + O. Astrochemical models predict typical NO abundances in the gas-phase, with respect to molecular hydrogen, of f (NO/H 2 ) E 10 À7 -10 À6 . The actual observed abundance 41 is about a factor 10 lower: f (NO/H 2 ) E 10 À8 .…”
Section: Introductionmentioning
confidence: 99%
“…Among the conclusions drawn by dB15 (page 12) is the following: "Comparing the current results with those of Boduch et al (2012), it seems that ozone is a good indicator for the presence of molecular oxygen, while nitrogen oxides give the best indication of the presence of molecular nitrogen mixed with water." Ozone certainly is made from molecular oxygen, but other sources exist, including CO 2 .…”
Section: Proposed Tracers For Astronomical Co 2 and N 2 +H 2 Omentioning
confidence: 78%
“…One can safely predict that the same products will be observed from other irradiated nitrogen-rich ices, such as N 2 +O 3 , NH 3 +O 2 , and so forth. For completeness, an ion-implantation study of Boduch et al (2012) should be mentioned here. It included two IR spectra of N 2 +O 2 after irradiation by 30 keV 13 C 2+ at 15 K, but neither an initial N 2 -to-O 2 ratio nor a radiation dose was given, and so that work is not included in our Table 5, although it too reported NO, NO 2 , and N 2 O formation.…”
Section: Reaction Chemistry In N 2 -Rich Icesmentioning
confidence: 99%